UN and peace discourse and the Palestine question : a critical discourse analysis - Assaiqeli, Aladdin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
Struggling in an age of Zionist dominance, of dominant Zionist discourse, it is maintained throughout this critical conscious-raising discourse study that the way the Palestine Question has been discursively constructed "along certain lines rather than others" is what has kept Palestine and the Middle East and much of the turbulence engulfing the world in the way it is now. It is also maintained that discourse is employed by the powerful to enact, normalise and sustain domination and control. Using the framework of Critical Discourse Analysis (CDA), the study has sought within the Discourse-Historical Approach (DHA) to examine UN resolutions and 'peace' discourses on the Palestine Question to find if they are bona fide and practical and accordingly whether they have contributed and if so in what ways and to what extent to the protracted status quo, and the abortive attempts of years of negotiations. The study has found that temporisation of the issue, of finding an amicable solution to the Palestine State problem was an indirect but calculated result of the bad faith and linguistic manipulation of the powerful forces; that those discursive practices are responsible for reproducing domination rather than trying to work out a "just, lasting and comprehensive" solution as articulated; that the way those discourses is structured does not lay the ground for justice and peace, but rather indefinite protraction of the Palestinian struggle against Israeli occupation where, given the current imbalance of power, the Palestinians would continuously remain the main "losers" within this form of social life. The study has detailed that the whole basis for the 'peace process' - UN Resolutions 242 and 338 - is flawed, mala fide and impractical in ending Israeli occupation and implementing th~, Palestinian refugees Right of Return and the Palestinian people Right to Self-Determination. So found to be little more than war against the powerless by other means, those UN resolutions and 'peace' discourses as they stand are meant in light of the bad faith underlying them to provide for the powerful the means to further consolidate their domination and control, and indefinitely. In this context, the study has revealed that the apparent pursuit of 'peace' as an American-Israeli means to sustain war (the status quo) need not be a paradox. The study draws its significance from its demonstration of the centrality of each of the Palestine Question to peace, discourse to power relations, and CDA to social change. The study is expected to make us, rulers and ruled, far conscious of domination in its linguistic forms, and of the role of those linguistic forms in the reproduction or transformation of the status quo.